2015
DOI: 10.4161/21505594.2014.988097
|View full text |Cite
|
Sign up to set email alerts
|

Candida parapsilosis produces prostaglandins from exogenous arachidonic acid and OLE2 is not required for their synthesis

Abstract: Prostaglandins are C20 fatty acid metabolites with diverse biological functions. In mammalian cells, prostaglandins are produced from arachidonic acid (AA) via cyclooxygenases (COX1 and COX2). Although fungi do not possess cyclooxygenase homologues, several pathogenic species are able to produce prostaglandins from host-derived arachidonic acid. In this study, we characterized the prostaglandin profile of the emerging human pathogen Candida parapsilosis with HPLC-MS and compared it to that of C. albicans. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 33 publications
(56 reference statements)
0
26
0
Order By: Relevance
“…As the incidence of this species has increased over the past two decades and the patient group at risk includes immunosuppressed children and adults as well as neonates, understanding the pathogenesis of C. parapsilosis has gained increased attention [16,28]. Preliminary studies have started to elucidate the prostaglandin profile of this species [17], however, the involved biosynthetic pathways and the presence or role of other fungal eicosanoids remained elusive. Previously, we have shown that in the presence of exogenous arachidonic acid, C. parapsilosis is capable of producing fungal prostaglandins, although OLE2 is not involved in the synthetic mechanisms, leaving the corresponding biosynthetic processes unexplored [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the incidence of this species has increased over the past two decades and the patient group at risk includes immunosuppressed children and adults as well as neonates, understanding the pathogenesis of C. parapsilosis has gained increased attention [16,28]. Preliminary studies have started to elucidate the prostaglandin profile of this species [17], however, the involved biosynthetic pathways and the presence or role of other fungal eicosanoids remained elusive. Previously, we have shown that in the presence of exogenous arachidonic acid, C. parapsilosis is capable of producing fungal prostaglandins, although OLE2 is not involved in the synthetic mechanisms, leaving the corresponding biosynthetic processes unexplored [17].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have started to elucidate the prostaglandin profile of this species [17], however, the involved biosynthetic pathways and the presence or role of other fungal eicosanoids remained elusive. Previously, we have shown that in the presence of exogenous arachidonic acid, C. parapsilosis is capable of producing fungal prostaglandins, although OLE2 is not involved in the synthetic mechanisms, leaving the corresponding biosynthetic processes unexplored [17]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both C. albicans and C. parapsilosis assimilate exogenic arachidonic acid in order to produce human prostaglandin-like molecules (PGE 2 and PGD 2 ) [47,48]. Fungal prostaglandins were shown to modulate host immune responses via a variety of mechanisms to promote host colonization [49].…”
Section: Function Of Fungal Secreted Lipasesmentioning
confidence: 99%
“…These cytokines include interleukin -1 (IL-1), interleukin -6 (IL-6) and tumor necrosis factor alpha (TNFα) as major inducers of inflammatory reactions; IL-8 as a neutrophil chemotactic factor and other chemokines to recruit leukocytes to the infection site [57,58]. Cyclooxygenase 2 (COX-2) is essential for the synthesis of the biologically active inflammation inducer prostaglandin E2 [48]. Toth A. et al and Nagy and Filkor et al reported that both DCs and PBMC-DMs released IL-1, IL-6 and TNFα pro-inflammatory cytokines at a markedly increased level in the presence Cp ΔΔlip1-ΔΔlip2 cells compared to that occurring in the presence of wild type yeast cells and an elevated level of IL-8 was detected after DCs were challenged with Cp ΔΔlip1-ΔΔlip2 compared to wild type cells [55].…”
Section: In Vitro Host Effector Cell -C Parapsilo-sis Interactionsmentioning
confidence: 99%